Morphological and biochemical markers of inflammatory reactions in a mucous membrane of bronchial tubes at the heavy form of a bronchial asthma and chronic obstructive disease of lungs - Ye. A. Gereng; I. V. Sukhodolo; R. I. Pleshko; L. M. Ogorodova; O. Ye. Akbasheva; Ye. B. Bukreyeva; A. N. Dzyuman; O. S. Kobyakova; P. A. Selivanova; I. S. Kremis (Бюллетень сибирской медицины, 2009)
In the present research the complex cytologic and biochemical estimation of a condition induced sputum at 19 patients with the heavy therapeutic-sensitive form of a bronchial asthma and 18 patients with chronic obstructive disease of lungs is lead. Dominating morphological and biochemical markers of an asthma became the raised number of macrophages, lymphocytes, and eosinophils at decrease in functional activity neutrophil elastase and increases activation properties. Progressing of destructive and fibrous processes at patients with heavy form chronic obstructive pulmonary disease occurs on a background active neutrophil and lymphocytes reactions in a mucous membrane of bronchial tubes that proves to be true high activity elastase and falling of functioning proteinase inhibitor.